PEMANFAATAN LIMBAH TUTUP BOTOL PLASTIK MENJADI KERAJINAN TANGAN YANG BERNILAI ESTETIKA DAN EKONOMI - Supriyatin, Titin; Nurazhimah Arfa, Avini; Islamay Hartono , Vernando (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The results of the observations carried out show that in the Andalusia residence sharia residential area, Gunung Putri Bogor, plastic waste from used drink bottles around us is increasing. The characteristics of plastic, which are lighter, more practical and easy to manufacture, have led to the large use of plastic. The increasing population in Indonesia also causes more plastic production. The plastic packaging used is then immediately thrown away without processing and becomes plastic waste. As a result of the increasing level of public consumption and other activities, the amount of waste produced is also increasing. Waste/disposal resulting from community activities and consumption is often called domestic waste or rubbish. The problem faced by the Partners of the Andalusia Residence Syariah Residents' Association is piles of plastic bottle waste. The piles of plastic bottle waste have not yet been utilized into something useful and become useful items. This is due to the local community's lack of knowledge in utilizing plastic bottle waste optimally so that it has economic value. One solution to overcome this is to make efforts to recycle waste, so that it is hoped that the volume of plastic waste can be reduced. Another problem faced by partners is the partners' limited knowledge about making handicrafts from plastic bottle waste. Therefore, our team's method of service is by holding training for partners with the theme of making various handicrafts through the use of recycled plastic drink bottle caps. From our team's community service activities we obtain products in the form of tissue holders, pencil boxes, photo frames and flower hangers from caps. bottle.mitra was very enthusiastic during the activity.